Analisis Pembentukan dan Makna Shouryakugo Pada Sosial Media : Kajian Morfosemantik - Masrokhah, Yuni; Natalia, Ana; Sofyan, Tasya (Vocational College of Diponegoro University, 2023)
There are various types of Japanese language, namely the variety of written language (kaki kotoba) and the variety of spoken language (hanashi kotoba). Shouryakugo is the process of word shortening, while the result of word shortening is called ryakugo. This shouryakugo often occurs when communicating orally, for example in anime, movies, advertisements and social media (Instagram, Twitter, Facebook etc.). So that foreign language learners, especially Japanese, find it difficult if there is an abbreviated vocabulary. Because Japanese language learners do not know about the process of abbreviating words, whether the word produces a new form but also acquires a new meaning called grammatical meaning, while the original meaning is a lexical meaning. Therefore, researchers aim to examine this in a study. Like the word セコンドハンド becomes セコハン(second hand). Analyzing shouryakugo in morphological and semantic studies, it is hoped that Japanese language learners will be able to use shouryakugo based on the process of formation, meaning and type in Japanese sentences. The theory used in this study uses Yonekawa's theory of the formation of Japanese morphology and Shouryakugo classification, on Social Media (Instagram, Twitter, Facebook, Youtube, etc.). The method in this study is a qualitative descriptive method. The data analysis technique used is the lethargy technique.